1986
DOI: 10.1109/tap.1986.1143893
|View full text |Cite
|
Sign up to set email alerts
|

A spiral antenna backed by a conducting plane reflector

Abstract: An Archiedean planar spiral antenna is numerically analyzed in the presence of a conducting plane reflector. The analysis shows that the spiral antenna backed by the plane reflector has two distinct regions in the current distribution, which explain the radiation of a circularly polarized wave for the outer circumference C ranging over shout 1.3 X < C < 1.5 A and C > 2.9 X, where A is a free-space wavelength. Further consideration is given to a truncated spiral antenna whose outer circumference is on the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(114 citation statements)
references
References 5 publications
2
110
0
2
Order By: Relevance
“…It is found that, as the aspect ratio decreases, the height needs to be increased. The dependence of AR performance on the antenna height above a ground plane has also been observed for other planar CP antennas, such as spiral antennas backed by a conducting plane reflector [19]. Our investigation reveals that a decrease in the antenna height changes the travelling-wave current distribution on driven loops, thus deteriorating the AR performance.…”
Section: Wideband Rectangular-loop Antennassupporting
confidence: 72%
“…It is found that, as the aspect ratio decreases, the height needs to be increased. The dependence of AR performance on the antenna height above a ground plane has also been observed for other planar CP antennas, such as spiral antennas backed by a conducting plane reflector [19]. Our investigation reveals that a decrease in the antenna height changes the travelling-wave current distribution on driven loops, thus deteriorating the AR performance.…”
Section: Wideband Rectangular-loop Antennassupporting
confidence: 72%
“…Thus, a bandwidth approximately from 2.8 GHz to 6.7 GHz is considered here in Figure 5. Figure 5 shows that the input reactance is close to zero in the radiation region, which is a well-known property of spiral antenna [7,10,16]. A clearly frequency-independent behavior of input impedance is observed on the self-complementary structure (χ = 0.5) over the bandwidth.…”
Section: Parametric Study Of Archimedean Spiral Antennamentioning
confidence: 74%
“…A number of numerical methods have been developed and utilized to model these broadband attributes. The method of moments (MoM) with thin-wire assumption is applied in several earlier works to investigate the spiral on an infinite reflector [7], impedance loading along the spiral arms [8], and monofilar spiral backed by a ground plane [9] in free space. The printed wire design can also be analysed by MoM on a semi-infinite dielectric substrate [10], an infinite conductor-backed substrate [11,12], and an infinite grounded substrate with superstrate [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that (15) and (16) do not include any calculations of integrals reduces the computational burden.…”
Section: Far-zone Fieldsmentioning
confidence: 99%